The impact of closed incisional negative pressure therapy on anterior lateral thigh flap donor site healing and scarring: A retrospective case-control study. Issue 1 (January 2022) - Falkner, Florian; Thomas, Benjamin; Mayer, Simon; Haug, Valentin; Harhaus, Leila; Nagel, Sarah; Kneser, Ulrich; Bigdeli, Amir K.
Summary: Background: The objective of this study was to investigate whether closed incisional negative pressure therapy (cINPT) is suitable to improve anterior lateral thigh (ALT) flap donor site healing and scarring. Methods: We identified 271 ALT free flaps of widths between 7 and 9 cm and primary donor site closure performed between January 2012 to December 2019. Patients were divided into cases of cINPT versus controls without cINPT as part of this retrospective case-control review. We compared the incidences of postoperative donor site complications (wound dehiscence, infection, seroma, hematoma) and the degree of scarring severity using the Vancouver Scar Scale (VSS) and the Patient and Observer Scar Assessment Scales (POSAS). Results: A total of 106 ALT donor sites received cINPT (39%), whereas the remaining 165 donor sites received conventional dressings (61%). The distribution of gender, age, body mass index, comorbidities, and mean flap sizes were comparable between both groups. The occurrence of surgical wound dehiscence was significantly lower in the cINPT group (2.8%), when compared to controls (9.0%) ( p = 0.04). Furthermore, the mean length of postoperative hospital stay was significantly shorter in the cINPT group (19 ± 8 days versus 21 ± 11 days; p = 0.03). CINPT was associated with a more favorable donor site scar quality when assessed by VSS ( p = 0.03) and POSAS ( p = 0.002). Conclusion: The use of cINPT was associated with significantly less ALT donor site complications and superior scar quality accelerating patients' postoperative recovery.